Time, identity and memory in the cinema of Christopher Nolan: a philosophical approach to the narrative keys of its staging - Álvarez Gómez, Raúl (2020)
Christopher Nolan's cinema highlights, among other aspects, a staging in which the spaces of representation (sets and natural scenes), cinematographic time (narrative time and time of history) and the identity of the characters are presented to the audience in a synchronic and fragmented style, like pieces of a puzzle on a table. This article aims to establish a connection between that narrative formula, which breaks the classical chronological and linear structure, and the consolidation after 11S of a philosophy of "love for the fragment" (Rella, 1998: 38), based on the different drifts of the Hegelian idealism, which challenges the belief in an absolute and unitary reason, in particular in the subjects related to the individual and the memory. It is a reflection of a philosophical rather than narrative nature aimed at situating and understanding Nolan's cinema in the thought coordinates of his time. Because his films do not aspire to offer answers to the big questions, but to ask new questions.